Adaptation of the developed country MNES business models to severe environments : the case of logistics companies in the DRC - Anger, Benoit (2015)
The DRC is a country with a huge economic potential but stuck in under development for several reasons such as weak institutions, the corruption, the political instability or the insecurity. Despite the opportunities, many developed country MNEs prefer to stay away from the country, as doing business in the DRC is tremendously challenging. However, experience showed that developed country MNEs can succeed in the country. In the context of globalization of the economy and given that LDCs are home of a significant share of the world population, it seems particularly relevant to investigate the question of how developed country MNEs can adapt their business model to operate successfully.